2019
DOI: 10.3390/rs11101252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drone Altitude, Image Overlap, and Optical Sensor Resolution on Multi-View Reconstruction of Forest Images

Abstract: Recent technical advances in drones make them increasingly relevant and important tools for forest measurements. However, information on how to optimally set flight parameters and choose sensor resolution is lagging behind the technical developments. Our study aims to address this gap, exploring the effects of drone flight parameters (altitude, image overlap, and sensor resolution) on image reconstruction and successful 3D point extraction. This study was conducted using video footage obtained from flights at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 31 publications
5
107
1
Order By: Relevance
“…The same applies to the dependency of optimal overlap configuration from the UAS sensor type. Similarly, [60] examined the connection between image overlap, the processing time, and low altitude flights, but the images were extracted from compressed MPEG-4 video as JPEG or PNG image files. This approach enables extremely high forward overlap (up to 98.8%) to be achieved without an increase in flying time, and proved to be beneficial in low altitude flights (15-30 m above the canopy).…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The same applies to the dependency of optimal overlap configuration from the UAS sensor type. Similarly, [60] examined the connection between image overlap, the processing time, and low altitude flights, but the images were extracted from compressed MPEG-4 video as JPEG or PNG image files. This approach enables extremely high forward overlap (up to 98.8%) to be achieved without an increase in flying time, and proved to be beneficial in low altitude flights (15-30 m above the canopy).…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…For instance, thermal surveys (which generally contain much less feature information than optical images), often require overlaps at least of 80% [51]. Therefore, this upper end of the image overlap range is adopted in cases where a high level of accuracy is required [56,57,59], while the lowest overlaps, for rapid observation with low accuracy requirements, should not be less than 55% [60]. Some studies have also found that interactions between flight collection variables, including flight altitude, image overlap, flying direction, speed and solar elevation affect UAS data quality and the subsequent processing results, emphasizing the need for flight planning optimization [61].…”
Section: Camera Settings and Uas Control Softwarementioning
confidence: 99%
“…Usually, before conducting aerial surveys, several parameters need to be optimized. These include flight altitude, image overlap, speed, resolution, and area of coverage [22]. Logically, higher flight altitude captures a smaller number of images with lower ground sample distance (GSD) because of the broad field of view of the camera sensors onboard the UAV.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of recent studies have confirmed the great potential of UAS photogrammetry in forest inventory, at both individual tree- [16,18] and plot-levels [14,[40][41][42][43][44][45]. In general, the quality of the obtained forest inventory data depends on the quality and accuracy of the UAS products (e.g., PCs, DSMs) and DTM, while the quality of the UAS products depends on the image block orientation method applied to UAV data, among other factors such as flight characteristics and target properties [62].…”
Section: Discussionmentioning
confidence: 99%